Investigation of behaviour styles of the coaches of athletes who competed at 2018 snowboard cross World Cup - Gül, M.; Birinci, M. C.; Agaoglu, S. A. (Universal Journal of Educational Research, 2019)
Coaches are one of the leading people who have a role in athletes' success. Physical and physiological characteristics of many elite athletes are close to each other. The most important psychological factor as the distinguishing element bringing success is the coaches' behavioral approaches to their athletes. It is important to find out the behavioural styles of the coaches of athletes who are representing their countries in international organizations and who are showing top level performance in increasing their countries' success. In this sense, the purpose of this study is to analyze the coaching behaviour styles of the coaches of snowboard cross athletes representing their countries in the world cup. The study is a descriptive study in the model of survey. 3-item personal information form developed by the researcher and Coaching Behaviour Scale for Sport- CBS-S consisting of 7 factors and 47 items were used as data collection tool. The scale was given to 68 of 97 athletes competing for different countries in Snowboard Cross World Cup that was held in Erzurum/ Turkey in January 2018. Percentage, frequency, mean and average values were used in the analysis of data. Various difference tests were used to find out the differences between variables. 24 female and 44 male athletes participated in the study. Average age of the athletes was found as 25,16±4,53. No significant difference was found in terms of the variables of age, gender and the continent athletes participated from and it was found that athletes assessed the positive behavioural styles of coaches in very high levels (6,98±1,21), while they assessed their negative coaching behaviours in very low levels (1,08±0,14). According to the results obtained, it is recommended for behavioural styles of coaches assessed within the context of similar researches to be applied to other sport branches.